(False) Dichotomies, political ideologies, and preferences for environmental management along the rural-urban interface in Calaveras County, California. (December 2015) - Hiner, Colleen C.
Abstract: At the core of land use and governance debates in the United States are purported dualities: economy vs. environment, public goods vs. private rights, and the merits and demerits of regulation. While such dichotomies are inevitably partial, they offer a heuristic to interrogate the deeper nuances of a problem or process. I investigate these dichotomies in one site (Calaveras County, California) along the rural-urban interface (RUI). The RUI is home of some of the most valued places in contemporary society as well as some of the most challenged in terms of planning and management. Land management decisions along the RUI are complicated by social and ecological heterogeneity as well as ongoing, dynamic cultural and environmental change. Differing perspectives and shifting conditions in place influence stakeholders' views on the value and utility of a variety of resources, both environmental and social. This paper investigates how political and environmental ideologies and environmental management preferences are related in order to consider the implications of such divergent perspectives for policy and governance. Using a mixed method approach, I examine varying viewpoints related to the environment/economy dichotomy and conclude that increasing polarization of political and environmental ideals and preferences along the RUI impacts land use planning and policy as well as social, environmental, and economic outcomes. I argue that the physical and cultural landscape of the RUI is transforming and, as such, we must also (re)configure pathways for cooperation and problem solving to effectively address the challenges and contradictions of these social and ecological changes. Highlights: Social and ecological heterogeneity and change complicate land management decisions along the rural-urban interface. Political and environmental ideologies influence perspectives of environmental governance and land use/management. Polarization of political and environmental preferences impacts land use planning/policy and social/environmental outcomes. Diverse perspectives should be welcomed and considered in landscapes of ideological difference and environmental conflict.